(untitled) (TAFSE: Journal of Qur’anic Studies, 2022)
One of the branches contested in the Musabaqah Tilawatil Qur’an (MTQ) is qira’at sab’ah. The existence of these religious festival activities aims to broadcast the values of the Koran in people’s lives so as to create generations who develop the qira`at of the Koran. However, in the qira`at sab’ah competition in Aceh, only the practice of reading was applied, not the knowledge of the science. This can be seen from the lack of mastery of the participants who took part in the qira`at sab’ah branch. This problem raises the question of how the teaching of qira`at science exists at LPTQ Aceh and the understanding of the theory of qira`at science for MTQ participants in the qira`at sab’ah branch. This research is a field study, and data is collected from interviews, observations, and documentation. The findings of this study indicate that teaching the science of qira’at is irregular, occurring only when the competition period approaches. Meanwhile, the level of understanding of qira`at sab’ah theory among MTQ participants in Aceh can be grouped into three categories: first, groups that understand the theories of qira`at science. Second, there is the group that does not understand the theories of qira`at science. Third, the group that does not understand the theories of qira’at science, but all participants are able to practice the reading taught by the teacher. Abstrak: Qira’at sab’ah merupakan salah satu cabang yang diperlombakan dalam Musabaqah Tilawatil Qur’an (MTQ). Adanya kegiatan festival keagamaan tersebut bertujuan untuk mensyiarkan nilai-nilai Al-Qur’an dalam kehidupan masyarakat, sehingga dapat menciptakan generasi-generasi yang mengembangkan qira`at Al-Qur’an. Akan tetapi, pada perlombaan qira`at sab’ah di Aceh, hanya diterapkan praktik bacaannya, bukan pengetahuan terhadap ilmunya. Hal ini terlihat dari minimnya penguasaan peserta yang mengikuti cabang qira`at sab’ah. Permasalahan ini menimbulkan pertanyaan bagaimana eksistensi pengajaran ilmu qira`at pada LPTQ Aceh dan pemahaman tentang teori ilmu qira`at bagi peserta MTQ cabang qira`at sab’ah. Penelitian ini merupakan kajian lapangan dan data dikumpulkan dari hasil wawancara, observasi dan dokumentasi. Hasil penelitian ini menunjukkan bahwa eksistensi pengajaran ilmu qira’at bersifat tidak reguler, dilakukan hanya ketika mendekati masa perlombaan. Sedangkan tingkat pemahaman teori qira`at sab’ah pada peserta MTQ di Aceh dapat dikelompokkan menjadi tiga kategori, pertama, kelompok yang paham teori-teori ilmu qira`at. Kedua, kelompok yang kurang paham teori-teori ilmu qira`at. Ketiga, kelompok yang tidak paham teori-teori ilmu qira`at, akan tetapi semua peserta mampu mempraktikkan bacaan yang diajarkan oleh guru.